Quantitative EEG in Schizophrenic Patients before and during Pharmacotherapy - Begić, Dražen (Array, 2000)
The aim of the study was to determine the possible differences in quantitative EEG parameters of schizophrenic patients before and during therapy with neuroleptics. First EEG recordings were obtained from schizophrenic patients (n = 50) who had not been taking any medicaments during the preceding 2 months. Second EEG recordings were obtained during the administration of neuroleptic therapy. Amplitude values of particular spectral segment, i.e. delta, theta, alpha 1, alpha 2, beta 1 and beta 2 (after fast Fourier transformation) were analyzed. The F3, F4, C3, C4, T3, T4, P3, P4, O1 and O2 regions were observed. The effect of pharmacotherapy manifested as a decrease in delta and beta 2 activities. The alterations of the delta spectrum were recorded in each patient subgroup (regardless of the neuroleptic used). The changes in beta 2 activity were registered in patients on haloperidol and fluphenazine.